Influencia de las proporciones de los agregados en el hormigón y la dosificación con cemento sobre el peso unitario y compresión en un concreto convencional - Soto Prado, Marco Antonio (2019)
At present, most of the buildings in the country are constructed without any technical criteria, omitting different factors that should be the subject of analysis to have safer and more durable structures over time, this type of buildings are called informal or self-construction, which use aggregates from different quarries, whose physical, chemical and mechanical properties are not known; in addition, many times for the elaboration of structural concrete hormigon is used that is a combination of gravel and sand in similar proportions as replacement of the aggregates classified because it is a more economic material, but that does not generate the levels of resistance desired in the concrete. The purpose of the investigation was to determine the optimal proportion of aggregates in the hormigon and at the same time their best dosage with cement, taking into account the expected resistance; for this purpose, proportions of 50-50 (A1), 60-40 (A2) and 70-30 (A3) were established in percentages of gravel with a maximum nominal size of 1" and sand with a fineness modulus of 2.4 respectively. Dosages were worked from 1:5 (B1) to 1:10 (B6) of cement: concrete (C:H), using red Mochica cement for general use. It is a question of giving an applicative approach to be used in field because the information is limited when working with proportions and dosages in volumetric quantities, generating a suitable recommendation for masters of work in self-construction on the quantities necessary to obtain good physical and mechanical properties of the concrete (unit weight and compression). Cylindrical concrete specimens (ASTM C31) of 15 x 30 cm, tested to compression (ASTM C39) and unit weight (ASTM C642) were formed. Specimens were tested at an age of 7, 14 and 28 days. The optimal design of concrete in volumetric proportions of cement and hormigon that fulfills the minimum resistance for structural elements was reached in the dosage 1:5, for a concrete with hormigon of proportions 70-30 in percentages of gravel and sand respectively, reaching a maximum value of 194 kg/cm2; however, the lightest concrete was achieved in the dosage 1:10 for the proportion 50-50 in percentages of gravel and sand, reaching a unit weight of 2272 kg/m3.